ASME 2012 Summer Bioengineering Conference, Parts a and B 2012
DOI: 10.1115/sbc2012-80805
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Model of the Thumb That Effectively Replicates Endpoint Forces Produced by Human Subjects and Measured in Anatomical Specimens

Abstract: Current biomechanical models of the thumb do not replicate either the maximum pinch forces produced via coordinated muscle actions by human subjects [1] or the magnitudes of the forces produced by individual muscles as quantified in cadaveric specimens [2]. However, compared to the literature, these models either underestimate the forces produced by human subjects [1] or overestimate the magnitudes quantified in cadaveric specimens [3, 4]. Specifically, the model developed by Valero-Cuevas et al (2003) was rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Those optimizations identified muscle anatomical parameters that were robust to local minima, consistent across animals, and physiologically realistic, suggesting that the isometric force measurements used in these experiments strongly constrain muscle model parameters. This approach has also been used to improve muscle moment arms for the thumb [14, 29]. Although we did not perform the same optimizations here, for many muscles the difference between measured and predicted forces appeared to be explicable by small alterations in muscle origins or insertions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those optimizations identified muscle anatomical parameters that were robust to local minima, consistent across animals, and physiologically realistic, suggesting that the isometric force measurements used in these experiments strongly constrain muscle model parameters. This approach has also been used to improve muscle moment arms for the thumb [14, 29]. Although we did not perform the same optimizations here, for many muscles the difference between measured and predicted forces appeared to be explicable by small alterations in muscle origins or insertions.…”
Section: Discussionmentioning
confidence: 99%
“…These rough measurements and subject-independent assumptions could lead to uncertainties in the estimate of limb configuration and therefore inaccuracies in the forces predicted by the model [11]. Previous studies modelling muscles in the human thumb have shown that such incorrect estimates in limb configuration could be a significant source of musculoskeletal model force prediction errors [1214]. In general, such errors in limb configuration will affect any musculoskeletal model evaluation comparing predicted and observed forces.…”
Section: Introductionmentioning
confidence: 99%